Phytophthora nicotianae에 의한 서향 역병 - 권진혁(Jin-Hyeuk Kwon); 지형진(Hyeong-Jin Jee); 박창석(Chang-Seuk Park) (Sigmulbyeong yeon'gu, 2005)
In 2002 and 2003, Phytophthora blight on Daphne odora occurred in fields at Waryong Mountain, Sacheon city, Korea. The disease usually initiated on the root and crown of the plant. Crown lesions began with light brown as water-soaking. Infection rate of the disease reached up to 60% in a heavily infested fields. The causal fungus was identified as Phytophthora nicotianae based on following mycological characteristics. Sporangium: readily formed in water, papillate, noncaducous, ovoid to spherical, 23~$56{×}$~34 $μm$ in size. Oogonium: spherical, smooth walled, 18~26 $μm$ in size. Oospore: aplerotic, globose, 16~24 $μm$ in size. Antheridium: amphigynous, unicellula, spherical. Chlamydospore: abundant, spherical, 16~32 $μm$ in size. Sexuality: heterothallic. Optimum growth temperature was about 25~$30^{°}C$. Pathogenicity of the isolate was confirmed on host plant and the fungus was identified as Phytophthora nicotianae. This is the first report of Phytophthora blight of Daphne odora in Korea. 2002년에서 2003년까지 경상남도 사천시 와룡산 기슭의 서향 재배포장에서 Phytophthora nicotianae에 의한 서향 역병이 발생하였다. 병징은 잎이 황화되면서 떨어지고 줄기 및 지제부워가 암갈색의 수침상으로 갈변되어 썩으면서 시들어 말라 죽는다. PDA 배지 상에서 균총은 전형적인 장미꽃 또는 거미집 형태를 나타내었고 균사생육은 느렸다. 유주자낭은 구형 또는 난형이며 많은 양의 후막포자를 형성하였으며, 크기는 23~$56{×}21$~$34μm$ 이었다. 유성생식형은 자웅이주이며, 후막포자는 구형이며 크기는 16~$32μm$이었다. 난포자는 비충만형으로 크기는 18~$26μm$ 이다. 장정기는 저착이며 구형이었다. 균사 생육적온은 25~$30^{°}C$ 였다.